Hall and Ion Slip Currents’ Impact on Electromagnetic Blood Flow Conveying Hybrid Nanoparticles Through an Endoscope with Peristaltic Waves - Das, S.; Barman, B.; Jana, R. N.; Makinde, O. D. (BioNanoScience, 2021)
In this paper, a theoretical study is conducted to examine the electromagnetic peristaltic pumping features of an electrically conducting non-Newtonian blood through an endoscope where the blood is treated as the ionic suspension of hybrid nanoparticles. Casson fluid model is employed to simulate the rheological characteristics of blood. This study is motivated by the need to explore the dual impacts of Hall and ion-slip currents on the peristaltic bloodstream. The heat transfer is analyzed by contemplating the effects of viscous and Ohmic dissipations. Blood is used as a base fluid and silver and aluminum oxide nanoparticles are dispersed in order to have a homogenous hybrid blood suspension which is an ionic solution. Casson fluid model is adopted to describe non-Newtonian characteristics of the blood flow. The model problem is transformed from the fixed frame to the wave frame and rendered non-dimensional by employing befitting non-dimensional variables. The leading governing partial differential equations (PDEs) are simplified under the restrictions of long wavelength and low Reynolds number. The resulting PDEs subject to the physical boundary conditions are solved analytically, and closed-form expressions for the axial velocity, temperature, axial pressure gradient, pressure rise, heat transfer coefficient, and stream function are derived by using DSolve function built-in command of Mathematica . The influences of dominant flow parameters on the physical flow characteristics are graphically illustrated and interpreted. Graphical results reflect that Hall and ion slip currents exert a significant modification on blood velocity and pressure characteristics in the endoscopic annulus. Hybrid nanoparticles concentration has a pivotal role in the heat-conducting nature of blood which is cardinal to life-support. The streamline patterns illustrating the blood flow characteristics are found to be more strongly affected by changing the form of waves. This research study is to be pertinent in nano-pharmaco-dynamics, electromagnetic biomimetic blood pumps, medical pumps for drug delivery systems, etc.